Embodied experiences in modern and contemporary art : re-thinking Ruskin’s modern art - Kusumawardhani, Suhita Arindyah (Nanyang Technological University, 2021)
This paper seeks to unpack the traditional ontological constraints and limits that have been imposed onto art, to situate the development of art movements in modern art and present-day contemporary art. This pursuit is instrumental in highlighting the paradox that exists in the liberation of art, that allows for the coexistence of subjective experiences and shared experiences. There exists no hierarchy in art. Instead, this paper argues for the case that art acts as a medium for the collection of qualitative data points on human experiences and the human psyche , pointing at the ongoing meaning-making process and process of knowledge acquisition art allows for. In order to do so, this paper will begin by looking into John Ruskin’s Modern Painters’ hierarchical approach to modern art, that imposes a metrics on the experience of art. Ruskin’s Modern Painter will be compared to the phenomenological understanding of the body in the world. This phenomenological understanding of embodied perceptions by Merleau-Ponty and the meaning-fulfilment process outlined by Husserl, double as accounts for the development and process of subversion that still persists in the modern and contemporary art scene.